Pengaruh Tenaga Kerja, Modal, dan Teknologi Terhadap Pendapatan Petani di Desa Mangkauk Kecamatan Pengaron Kabupaten Banjar - Anggoro, Rio; Suherty, Lina (PPJP ULM, 2025)
This research aims to determine the influence of labor, capital and technology on farmers' income in Mangkauk Village, Pengaron District, Banjar Regency. This research was carried out in Mangkauk Village, Pengaron District, Banjar Regency with a sample size of 81 farmers. This research was conducted from September to December 2023. The data obtained from sample farmers was analyzed quantitatively or by multiple linear regression analysis. The research results show: (1) Based on the research results, labor partially has a positive and significant effect on farmers' income. (2) Based on the research results, capital partially has a positive and significant effect on farmers' income in Mangkauk Village, Pengaron District, Banjar Regency. (3) Based on research results, technology partially has a positive and significant effect on farmers' income.